Direitos políticos entre a democracia e o autoritarismo - Christiane Costa Assis (2022)
This thesis aims to analyze the capture of political rights and democracy by hybrid regimes that manage to operate within democratic rules. After ascending to power through elections, these apparently democratic governments begin a gradual process of erosion of democracy to repeat their victory at the elections revealing a paradox of political rights: the government is elected through them and then begins a process of capture of these rights to prevent opponents from winning elections. The scenario described combines two initially opposed regimes: democracy and authoritarianism. The result is hybrid regimes marked by particularities and ambiguities that make it difficult to perceive the democratic backsliding promoted by these governments. In this context, the thesis questions what are the possible solutions for democracy to prevail in face of the strategies executed by hybrid regimes. In the methodological aspect, the deductive research method was adopted, starting from fundamental considerations about democracy and then analyzing the democratic erosion in its different dimensions and identifying possible solutions. Documentary and bibliographical research techniques were also adopted, analyzing both legislation and scientific works in the researched theme. As a result, it is pointed out that the barrier against democratic erosion involves, notably, a collective conscience about the importance of democracy. A democratic commitment is needed between the State, society, the private sector and all institutions and entities in a scenario of plurality of interests. The diffusion of democratic values and the defense of democracy need to be a shared and continuous responsibility, going beyond perspectives centered on the role of the State that push into the background the importance of the commitment of private actors.